Novel design of high-surface-area poly-hollow alumina spheres via a facile ball dropping method based on particle-stabilized emulsions. Issue 17 (1st December 2019) - Li, Yajie; Gan, Ke; Huo, Wenlong; Liu, Kele; Liu, Jingjing; Wang, Xiuhui; Yu, Hongbo; Yang, Jinlong
Abstract: Herein, the preparation of millimeter-sized poly-hollow alumina spheres (PHASs) with high-surface-area is proposed via an innovative and facile ball dropping method based on particle-stabilized emulsions. The PHASs fabricated by this method possess high specific surface area because of their hierarchical pore structures and high porosity, and exhibit remarkable superiority over the commercially available active alumina materials with specific surface areas of 200–300 m 2 g -1 . The resultant millimeter-sized PHASs have diameters in range of 2–6 mm, average mesoporous sizes of 4–8 nm, and excellent specific surface areas of 400–500 m 2 g -1, which are achieved with oil-water volume ratio of 3:1, rotation speed of 900 rpm, and sintering temperature of 500 °C. These high-performance PHASs with ultra-high specific areas and hierarchical pore structures can potentially be useful in various applications.